Thompson calf squeezing test: clinical and ultrasound correlations in the follow up of Achille’s tenorraphy - Leigheb, M.; Conte, P.; Neri, P.; Zorzolo, I.; Martinelli, D.; Martino, F.; Carriero, A.; Grassi, F. (Acta Biomedica Atenei Parmensis, 2014)
In the follow up of Achille’s tenorraphy, negativization of Thompson calf queezing test is not always omogeneous and absolute. Aim of the paper is to correlate Thompson test to different anatomical-ultrasound and functional parameters. We investigated clinically and by ultrasound 61 patients operated on of Achille’s tenorraphy at Novara Hospital with follow-up of 10 to 46 months. Negative controls were contralateral tendons. We excluded patients with previous and/or contralateral Achille’s tendon ruptures, those operated after 7 days, diabetics or with autoimmune diseases, if used topic steroids, < 18 years, those rejecting the study. Measured parameters were: age, gender, height, weight, side, open vs percutaneous approach, time from operation, neutral angle and range of motion of the ankle, maximal circumference of the leg, Single Heel Rise Test, Visual-Analogue-Scale Foot and Ankle (VAS FA) score; with ultrasound: length of tendons, mio-tendinous U.S.-structure, dynamic diastasis of tendon scar, tendon sliding. Thompson test is positive if no plantar-flexion of the foot occurs at calf squeezing, negative if plantar-flexion is normal (75% patients) and intermediate if reduced or slight reactive (25%).We found correlation of Thompson test with age (p<0,05) and with tendon length (p>0,05), being intermediate tests more represented in older patients and in those with longer healed tendons. In conclusion post-operative negativization of Thompson test can be incomplete as observed in older patients and in those healed with elongated tendon.